The Discourse Strategies of GoJek Advertisement “Cerdikiawan” on YouTube - Widodo, Kartika; Ariyanti, Lisetyo (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2025)
This research focuses on the discourse strategies, social features, and socio-cultural aspects employed in a GoJek advertising video on YouTube. The study adopts Critical Discourse Analysis (CDA) within Fairclough's three-dimensional framework to understand the linguistic choices, social features, and how sociocultural elements persuade the audience. The paper outlines the descriptive qualitative methodology, including discourse and visual analysis. The analysis highlights rhetorical devices, figurative language, and social features as persuasive elements in the GoJek advertisement. This study contributes to understanding how discourse strategies and social features are used in advertising to influence audience perceptions and behaviors. The findings of the study indicate that GoJek's